2023
DOI: 10.3390/cancers15082238
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic Profiling Reveals Biological Differences between Tumors of Self-Identified African Americans and Non-Hispanic Whites with Cancer

Abstract: In the US, the incidence and mortality of many cancers are disproportionately higher in African Americans (AA). Yet, AA remain poorly represented in molecular studies investigating the roles that biological factors might play in the development, progression, and outcomes of many cancers. Given that sphingolipids, key components of mammalian cellular membranes, have well-established roles in the etiology of cancer progression, malignancy, and responses to therapy, we conducted a robust mass spectrometry analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 80 publications
0
0
0
Order By: Relevance
“…We suggest that the contrasting effects of GBA deletion, particularly those in hepatocellular carcinoma, are likely due to differences in the molecular alterations of sphingolipids that take place during transformation in these histologically different tumor-derived cell lines. This is supported by our previous data showing that hepatocellular tumors have significantly decreased GlcCer and LacCer [8], opposite of what we observed in SCC tumors and other tumor histologies where they are increased [8,9]. On the basis of the difference in phenotypic sensitivity of GBA KO hepatocellular carcinoma and SCC cells to GlcCer synthase inhibition, we speculate that malignancy associated with alterations in sphingolipid metabolism are driven by the activity of GlcCer synthase in hepatocellular carcinoma, and by GBA activity in SCC and ovarian cancer-derived cells.…”
Section: Differential Effect Of Gba Depletion In Various Cancer Cell ...supporting
confidence: 88%
See 4 more Smart Citations
“…We suggest that the contrasting effects of GBA deletion, particularly those in hepatocellular carcinoma, are likely due to differences in the molecular alterations of sphingolipids that take place during transformation in these histologically different tumor-derived cell lines. This is supported by our previous data showing that hepatocellular tumors have significantly decreased GlcCer and LacCer [8], opposite of what we observed in SCC tumors and other tumor histologies where they are increased [8,9]. On the basis of the difference in phenotypic sensitivity of GBA KO hepatocellular carcinoma and SCC cells to GlcCer synthase inhibition, we speculate that malignancy associated with alterations in sphingolipid metabolism are driven by the activity of GlcCer synthase in hepatocellular carcinoma, and by GBA activity in SCC and ovarian cancer-derived cells.…”
Section: Differential Effect Of Gba Depletion In Various Cancer Cell ...supporting
confidence: 88%
“…We previously showed that GlcCer of various acyl chain lengths are significantly increased in the tumors of patients with lung adenocarcinoma, lung squamous cell carcinoma (SCC), head and neck SCC, endometroid endometrial carcinoma, and colorectal adenocarcinoma [8][9][10]. Yet, as we show in this report, GBA copy number amplifications and increased protein and mRNA expression are common features in tumors of these and many other human cancers.…”
Section: Introductionsupporting
confidence: 50%
See 3 more Smart Citations